Strain Types and Antimicrobial Resistance Patterns of Clostridium difficile Isolates from the United States, 2011 to 2013 - Tickler, Isabella A. (American Society for Microbiology, 2014)
We determined the PCR ribotypes and antimicrobial susceptibility patterns of 508 toxigenic Clostridium difficile isolates collected between 2011 and 2013 from 32 U.S. hospitals. Of the 29 PCR ribotypes identified, the 027 strain type was the most common (28.1%), although the rates varied by geographic region. Ribotype 014/020 isolates appear to be emerging. Clindamycin and moxifloxacin resistances (36.8% and 35.8%, respectively) were the most frequent resistance phenotypes observed. Reduced susceptibility to vancomycin was observed in 39.1% of 027 isolates.